2016
DOI: 10.1038/srep31917
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism in intestinal epithelial cells during maturation along the crypt-villus axis

Abstract: Intestinal epithelial cells continuously migrate and mature along crypt-villus axis (CVA), while the changes in energy metabolism during maturation are unclear in neonates. The present study was conducted to test the hypothesis that the energy metabolism in intestinal epithelial cells would be changed during maturation along CVA in neonates. Eight 21-day-old suckling piglets were used. Intestinal epithelial cells were isolated sequentially along CVA, and proteomics was used to analyze the changes in proteins e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 32 publications
3
57
0
2
Order By: Relevance
“…This is in agreement with previous study, which concluded that the VH was related to the nutritional state in rats (Infante, Rouanet, & Besancon, ). That could be due to the ADFI, because it had been reported that insufficient energy intake is a major factor accounting for villous atrophy (Wang et al, ; Xiong, Yang, Tan, et al, ; Yang, Wang, Xiong, & Yin, ; Yang, Xiong, Wang, Li, & Yin, ). Marion et al () also reported that shortened small intestinal villus associates with absorptive capacity reductions.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous study, which concluded that the VH was related to the nutritional state in rats (Infante, Rouanet, & Besancon, ). That could be due to the ADFI, because it had been reported that insufficient energy intake is a major factor accounting for villous atrophy (Wang et al, ; Xiong, Yang, Tan, et al, ; Yang, Wang, Xiong, & Yin, ; Yang, Xiong, Wang, Li, & Yin, ). Marion et al () also reported that shortened small intestinal villus associates with absorptive capacity reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic growth parameters, including weight and length, were greater on day 7 and 14 post‐weaning, which is similar to previous studies (Marion, Biernat, Thomas, Le, & Zabielski, ; Tsukahara et al, ). Sufficiently rapid gut epithelium renewal, such as proliferation and differentiation, is a pre‐requisite for colon normal growth (Kohlnhofer, Thompson, Walker, & Battle, ; Yang, Wang, Xiong, & Yin, ). Crypt fission, which creates new crypts, is an alternate means of increasing intestinal tissue mass (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies performed by different authors indicate high respiratory activity of the intestinal mucosa of experimental animals, which corresponds to the intestine as a highly aerobic organ with a high intensity of energy exchange [17,18].…”
Section: Discussionmentioning
confidence: 99%